Pemberdayaan Masyarakat Melalui Kegiatan Teknis Pelatihan Jasa Desain Poster Makanan dan Minuman Melalui Market Place River - Heru Winarno; Syaina Ulfah Azhara (Universitas Teknologi Yogyakarta, 2024)
Student Work Lectures (KKM) are a form of community service activities by students and lecturers with a cross-scientific and sectoral approach at certain times and areas in areas/locations that are not yet developed. The development of the social, information and technology sectors in rural areas faces various challenges. Several technical and non-technical factors also become obstacles in current and future development. The provision of employment opportunities is limited, relying only on the agricultural sector, so that provisions and community capabilities are needed in providing business premises. This is done because the technological era in the eyes of society plays a very important role in empowering efforts to master information technology so that it is needed to facilitate independent business. Providing training and skills provision in the form of training on Food and Beverage Poster Design Services through Place Fiver Mockups. The aim of this activity is to provide knowledge and skills about design services so that they can be used as skills to be able to work independently and open business opportunities in the region. The research method used in this research is a case study with a qualitative approach and the data collection techniques used are observation, question and answer and documentation. The results of KKM activities are providing training and mentoring activities so that people in the regions can receive training provisions and are able to develop the training for future provisions.